A practical approach for the non-local simulation of progressive damage in quasi-isotropic fibre-reinforced composite laminates. (1st June 2021) - Reiner, Johannes
Abstract: This paper presents a generic strategy to generate macroscopic continuum damage models using non-local averaging. Formulation and derivation of such model are shown for dispersed quasi-isotropic IM7/8552 carbon fibre-reinforced composites. Experimental data and results from local damage simulations in over-height compact tension and compact compression tests are used to calibrate the non-local model for the simulation of progressive damage. A wide range of open–hole tension and compression tests validate these results. Thereby, different averaging radii are assessed in terms of prediction accuracy and computational efficiency. Besides the derivation of a practical relation of non-local damage parameters and fracture energy, it is shown that in these applications, non-local modelling enables the simulation of more realistic, mesh-independent damage. It is further concluded that the non-local averaging radius should be chosen to be small enough to avoid a significant increase of computational cost compared to local simulation methods.